Syntheses of 3,4- and 1,4-dihydroquinazolines from 2-aminobenzylamine - Díaz, Jimena E.; Ranieri, Silvia; Gruber, Nadia; Orelli, Liliana R. (Beilstein Journal of Organic Chemistry, 2017)
A straightforward strategy for the synthesis of dihydroquinazolines is presented, which allows for the preparation of 3,4- and 1,4-dihydroquinazolines with different substitution patterns from 2-aminobenzylamine (2-ABA) as common precursor. The required functionalization of both amino groups present in 2-ABA was achieved by different routes involving selective N-acylation and cesium carbonate-mediated N-alkylation reactions, avoiding protection/deprotection steps. The heterocycles were efficiently synthesized in short reaction times by microwave-assisted ring closure of the corresponding aminoamides promoted by ethyl polyphosphate (PPE).
Keywords: dihydroquinazolines; microwaves; N-acylations; N-alkylations; PPE

(untitled) - Baumann, M.; Baxendale, I. R.; Ley, S. V.; Nikbin, N. (Beilstein J. Org. Chem., 2011)

(untitled) - Baumann, M.; Baxendale, I. R. (Beilstein J. Org. Chem., 2013)

(untitled) - Doyle, M. E.; Egan, J. M. (Pharmacol. Rev., 2003)

(untitled) - Szabo, B. (Pharmacol. Ther., 2002)

(untitled) - Austin, W. C.; Courtney, W.; Danilewicz, J. C.; Morgan, D. H.; Conover, L. H.; Howes, H. L., Jr; Lynch, J. E.; McFarland, J. W.; Cornwell, R. L.; Theodorides, V. J. (Nature, 1966)

Approaches to Design and Synthesis of Antiparasitic Drugs - Anand, N.; Sharma, S. (Elsevier, 1997)

(untitled) - Meyer, E. M.; Arendash, G. W.; Judkins, J. H.; Ying, L.; Wade, C.; Ken, W. R. (J. Neurochem., 1987)

(untitled) - Weinhardt, K.; Wallach, M. B.; March, M. (J. Med. Chem., 1985)

(untitled) - Dunbar, P. G.; Durant, G. J.; Fang, Z.; Abuh, Y. F.; El-Assadi, A. A.; Ngur, D. O.; Periyasamy, S.; Hoss, W. P.; Messer, W. S., Jr (J. Med. Chem., 1993)

(untitled) - Dunbar, P. G.; Durant, G. J.; Rho, T.; Ojo, B.; Huzl, J. J., III; Smith, D. A.; El-Assadi, A. A.; Sbeih, S.; Ngur, D. O. (J. Med. Chem., 1994)

(untitled) - Los, R.; Wesołowska-Trojanowska, M.; Malm, A.; Karpińska, M. M.; Matysiak, J.; Niewiadomy, A.; Głaszcz, U. (Heteroat. Chem., 2012)

(untitled) - Li, W.-J.; Li, Q.; Liu, D.-L.; Ding, M.-W. (J. Agric. Food Chem., 2013)

(untitled) - Lee, Y. S.; Lee, B. H.; Park, S. J.; Kang, S. B.; Rhim, H.; Park, J.-Y.; Lee, J.-H.; Jeong, S.-W.; Lee, J. Y. (Bioorg. Med. Chem. Lett., 2004)

(untitled) - Heo, J. H.; Seo, H. N.; Choe, Y. J.; Kim, S.; Oh, C. R.; Kim, Y. D.; Rhim, H.; Choo, D. J.; Kim, J.; Lee, J. Y. (Bioorg. Med. Chem. Lett., 2008)

(untitled) - Byun, J. S.; Sohn, J. M.; Leem, D. G.; Park, B.; Nam, J. H.; Shin, D. H.; Shin, J. S.; Kim, H. J.; Lee, K.-T.; Lee, J. Y. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Ghosh, A. K.; Pandey, S.; Gangarajula, S.; Kulkarni, S.; Xu, X.; Rao, K. V.; Huang, X.; Tang, J. (Bioorg. Med. Chem. Lett., 2012)

(untitled) - Patterson, S.; Alphey, M. S.; Jones, D. C.; Shanks, E. J.; Street, I. P.; Frearson, J. A.; Wyatt, P. G.; Gilbert, I. H.; Fairlamb, A. H. (J. Med. Chem., 2011)

(untitled) - Tian, Y.; Ma, C.; Feng, L.; Zhang, L.; Hao, F.; Pan, L.; Cheng, M. (Arch. Pharm., 2012)

(untitled) - Decker, M. (Eur. J. Med. Chem., 2005)

(untitled) - Jaén, J. C.; Gregor, V. E.; Lee, C.; Davis, R.; Emmerling, M. (Bioorg. Med. Chem. Lett., 1996)

(untitled) - Armarego, W. L. F. (J. Chem. Soc., 1961)

(untitled) - Armarego, W. L. F. (Adv. Heterocycl. Chem., 1963)

(untitled) - Smith, J. G.; Sheepy, J. M. (J. Heterocycl. Chem., 1975)

(untitled) - Richers, M. T.; Zhao, C.; Seidel, D. (Beilstein J. Org. Chem., 2013)

(untitled) - He, K.-H.; Tan, F.-F.; Zhou, C.-Z.; Zhou, G.-J.; Yang, X.-L.; Li, Y. (Angew. Chem., 2017)

(untitled) - Burdick, B. A.; Benkovic, P. A.; Benkovic, S. J. (J. Am. Chem. Soc., 1977)

(untitled) - Papadopoulos, E. P.; George, B. (J. Org. Chem., 1977)

(untitled) - Grasso, S.; Micale, N.; Monforte, A.-M.; Monforte, P.; Polimeni, S.; Zappalà, M. (Eur. J. Med. Chem., 2000)

(untitled) - Zhang, J.; Barker, J.; Lou, B.; Saneii, H. (Tetrahedron Lett., 2001)

(untitled) - Baxter, E. W.; Conway, K. A.; Kennis, L.; Bischoff, F.; Mercken, M. H.; De Winter, H. L.; Reynolds, C. H.; Tounge, B. A.; Luo, C.; Scott, M. K.; Huang, Y.; Braeken, M.; et al. (J. Med. Chem., 2007)

(untitled) - Hsu, H.-Y.; Tseng, C.-C.; Matii, B.; Sun, C.-M. (Mol. Diversity, 2012)

(untitled) - Mercan, D.; Çetinkaya, E.; Şahin, E. (Inorg. Chim. Acta, 2013)

(untitled) - Li, C.; An, S.; Zhu, Y.; Zhang, J.; Kang, Y.; Liu, P.; Wang, Y.; Li, J. (RSC Adv., 2014)

(untitled) - Hati, S.; Sen, S. (Synthesis, 2016)

(untitled) - Kumar, R. A.; Saidulu, G.; Sridhar, B.; Liu, S. T.; Reddy, K. R. (J. Org. Chem., 2013)

(untitled) - Zhong, Y.; Wang, L.; Ding, M.-W. (Tetrahedron, 2011)

(untitled) - He, P.; Wu, J.; Nie, Y.-B.; Ding, M.-W. (Eur. J. Org. Chem., 2010)

(untitled) - Charton, J.; Girault-Mizzi, S.; Debreu-Fontaine, M.-A.; Foufelle, F.; Hainault, I.; Bizot-Espiard, J.-G.; Caignard, D.-H.; Sergheraert, C. (Bioorg. Med. Chem., 2006)

(untitled) - Dietrich, J.; Kaiser, C.; Meurice, N.; Hulme, C. (Tetrahedron Lett., 2010)

(untitled) - Nakagawa, Y.; Stevenst, R. V. (J. Org. Chem., 1988)

(untitled) - Lv, Y.; Li, Y.; Xiong, T.; Pu, W.; Zhang, H.; Sun, K.; Liu, Q.; Zhang, Q. (Chem. Commun., 2013)

(untitled) - Kreher, R.; Bergmann, U. (Heterocycles, 1981)

(untitled) - Hoang, L. T. M.; Ngo, L. H.; Nguyen, H. L.; Nguyen, H. T. H.; Nguyen, C. K.; Nguyen, B. T.; Ton, Q. T.; Nguyen, H. K. D.; Cordova, K. E.; Truong, T. (Chem. Commun., 2015)

(untitled) - Yadav, D. K. T.; Bhanage, B. M. (Synlett, 2015)

(untitled) - Pelagalli, R.; Chiarotto, I.; Feroci, M.; Vecchio, S. (Green Chem., 2012)

(untitled) - Apfel, C.; Banner, D. W.; Bur, D.; Dietz, M.; Hubschwerlen, C.; Locher, H.; Marlin, F.; Masciadri, R.; Pirson, W.; Stalder, H. (J. Med. Chem., 2001)

(untitled) - Rzasa, R. M.; Kaller, M. R.; Liu, G.; Magal, E.; Nguyen, T. T.; Osslund, T. D.; Powers, D.; Santora, V. J.; Viswanadhan, V. N.; Wang, H.-L.; Xiong, X.; Zhong, W.; et al. (Bioorg. Med. Chem., 2007)

(untitled) - Bar-Haim, G.; Kol, M. (Tetrahedron Lett., 1998)

(untitled) - Coyne, W. E.; Cusic, J. W. (J. Med. Chem., 1968)

(untitled) - Camacho, M. E.; Chayah, M.; García, M. E.; Fernández-Sáez, N.; Arias, F.; Gallo, M. A.; Carrión, M. D. (Arch. Pharm., 2016)

(untitled) - Farhanullah; Samrin, F.; Ram, V. J. (Tetrahedron, 2009)

(untitled) - López, S. E.; Restrepo, J.; Salazar, J. (J. Chem. Res., 2007)

(untitled) - Kanaoka, Y.; Kuga, T.; Tanizawa, K. (Chem. Pharm. Bull., 1970)

(untitled) - Kanaoka, Y.; Yonemitsu, O.; Sato, E.; Ban, Y. (Chem. Pharm. Bull., 1968)

Microwave-Assisted Synthesis of Heterocycles - Van der Eicken, E.; Kappe, C. O. (Distribution Center, GmbH, 2006)

(untitled) - Bougrin, K.; Loupy, A.; Soufiaoui, M. (J. Photochem. Photobiol., C: Photochem. Rev., 2005)

(untitled) - Sharma, A.; Appukkuttan, P.; Van der Eycken, E. (Chem. Commun., 2012)

(untitled) - García, M. B.; Torres, R. A.; Orelli, L. R. (Tetrahedron Lett., 2006)

(untitled) - Díaz, J. E.; Bisceglia, J. Á.; Mollo, M. C.; Orelli, L. R. (Tetrahedron Lett., 2011)

(untitled) - Díaz, J. E.; Gruber, N.; Orelli, L. R. (Tetrahedron Lett., 2011)

(untitled) - Díaz, J. E.; Mollo, M. C.; Orelli, L. R. (Beilstein J. Org. Chem., 2016)

(untitled) - Mollo, M. C.; Orelli, L. R. (Org. Lett., 2016)

(untitled) - Link, N. P.; Díaz, J. E.; Orelli, L. R. (Synlett, 2009)

(untitled) - Nivsarkar, M.; Kaushik, M. P. (Catal. Commun., 2005)

(untitled) - Pollmann, W.; Schramm, G. (Biochim. Biophys. Acta, 1964)

(untitled) - Brain, K. R.; Thapa, B. B. (J. Chromatogr., 1983)